The Poisson-exponential regression model under different latent activation schemes - Louzada, Francisco; Cancho, Vicente G; Barriga, Gladys Dorotea Cacsire [UNESP] (Sociedade Brasileira de Matemática Aplicada e Computacional, 2012)
In this paper, a new family of survival distributions is presented. It is derived by considering that the latent number of failure causes follows a Poisson distribution and the time for these causes to be activated follows an exponential distribution. Three different activationschemes are also considered. Moreover, we propose the inclusion of covariates in the model formulation in order to study their effect on the expected value of the number of causes and on the failure rate function. Inferential procedure based on the maximum likelihood method is discussed and evaluated via simulation. The developed methodology is illustrated on a real data set on ovarian cancer. Mathematical subject classification: 62N01, 62N99.
Keywords: activation schemes; exponential distribution; poisson distribution; survival analysis